PERAN PENDIDIKAN DALAM MENCERDASKAN MASYARAKAT - Wa Ode Murima La Ode Alumu (Foramadiahi: Jurnal Kajian Pendidikan dan Keislaman, 2019)
Education is an instrument for development and empowering society, wich should be prominently laid on the endewors to in crease faith (iman),  piety ( taqwa), as well as morals ( akhlaq). Here, the religion led to be a basis for establishing welfare society on the earth, and for securing hehe after-life. As a consequence, the development of science and technology, on the other direction, must be persistently harmonized with those religious values. Within such relationship, religion is required as  a principal mean for  directing the development of on the use of science and technology